2 - Réforme LMD au Maghreb : éléments pour un premier bilan politique et pédagogique - Ahmed Ghouati (Journal of Higher Education in Africa, 2009)
Three years after the release (extension) of the process from Bologna to the Maghreb – Notably in Algeria, in Morocco and more recently in Tunisia –, is a first balance sheet (assessment) possible? The main institutional actors and the decision-makers met in December 2006 to draw up their own balance sheet (assessment). Politically, the process was considered successful. That is why, for lack of tangible educational quantitative and qualitative results, the people in charge agreed to deepen politically the process through the creation of a French-speaking Academic School Euro-Maghrebin ( CAUFEM ). This school has among others functions (offices) to follow and to harmonize the current reforms, in particular the reform LMD. Nevertheless, on an educational plan, from little of available statistics and qualitative appreciations collected with academics from the Maghreb, it seems to us that this reform is far from having the success expected with the students and the teachers. Where from the hypothesis according to which the process of Bologna is more intended to integrate, by the height and by the arguments of authority, the space from the Maghreb of higher education and of research in the European space. This integration wants to facilitate the mobility in the South-North direction to enrich the European fishpond (pool) in highly Qualified Workers and allow a control of the university field and its orientation according to political and economic objectives defined, except the main actors of the systems of higher education.